Chile’s Forests : A Pillar for Inclusive and Sustainable Development - World Bank (World Bank, Washington, DC, 2020)
Since the beginning of the twentieth century, Chile embarked on a long journey to develop a forestry model adapted to its national circumstances, achieving considerable progress in the last four decades by significantly increasing its forest cover and developing a highly competitive industry with global reach, making forestry among the country’s main economic activities. Despite the significant achievements made in establishing a vast natural capital based of planted forests in the country, the forest sector faces new challenges. The effects of climate change with increasing temperatures and decreasing precipitation are accelerating desertification, land degradation and drought processes. Furthermore it is increasing the frequency and intensity of forest fires, affecting the quality of life of hundreds of thousands of people, the future availability of timber, and generating a variety of other impacts on the country's ecosystems. This new scenario also entails the need to strengthen, modernize and adapt the current institutional framework to enable it to more effectively support the continuous growth of the forest sector in the current national and global context, and continue generating economic, social and environmental benefits for the country.